Spreading of a ferrofluid core in three-stream micromixer channels - Wang, Zhaomeng (2015)
Spreading of a water based ferrofluid core, cladded by a diamagnetic fluid, in three-stream micromixer channels was studied. This spreading, induced by an external magnetic field, is known as magnetofluidic spreading (MFS). MFS is useful for various novel applications where control of fluid-fluid interface is desired, such as micromixers or micro-chemical reactors. However, fundamental aspects of MFS are still unclear, and a model without correction factors is lacking. Hence, in this work, both experimental and numerical analyses were undertaken to study MFS. We show that MFS increased for higher applied magnetic fields, slower flow speed of both fluids, smaller flow rate of ferrofluid relative to cladding, and higher initial magnetic particle concentration. Spreading, mainly due to connective diffusion, was observed mostly near the channel walls. Our multi-physics model, which combines magnetic and fluidic analyses, showed, for the first time, excellent agreement between theory and experiment. These results can be useful for lab-on-a-chip devices.